KEPERCAYAAN MASYARAKAT TERHADAP UPACARA ADAT TEING HANG BAGI PARA LELUHUR DI DESA GOLO, KECAMATAN CIBAL, KABUPATEN MANGGARAI (STUDI KASUS DI DESA GOLO, KECAMATAN CIBAL, KABUPATEN MANGGARAI) - Yohana Fatima Hibur; Dewa Bagus Sanjaya; I Gusti Ketut Arya Sunu (Program Studi PPKn Jurusan Hukum dan Kewarganegaraan Undiksha Singaraja, 2022)
This study aims to find out (1) the philosophy of the Teing Hang traditional ceremony for the people in Golo Village, Cibal District, Manggarai Regency, (2) how the process of implementing the Teing Hang traditional ceremony for the people in Golo Village, Cibal District, Manggarai Regency, (3) character values ​​in the Teing Hang traditional ceremony for the community in Golo Village, Cibal District, Manggarai Regency, (4) the usefulness of the Teing Hang traditional ceremony on people's lives in Golo Village, Cibal District, Manggarai Regency. This study used descriptive qualitative method. Data collection techniques used are interviews, observation, and documentation. The research subjects were determined by purposive sampling technique, the subjects of the research were: traditional elders and the community. The results of this study show the philosophy of the Teing Hang traditional ceremony to ask for success, ask for protection and in the form of thanks giving. In the process of carrying out the Teing Hang ceremony starting with the opening ceremony, the two Torok speakers accept the purpose of the Teing Hang ceremony, the three Teing Hang ceremonies begin, the fourth Torok. The character values ​​contained in the Teing Hang traditional ceremony are the values ​​of God Almighty (Religion), just and civilized human values, the value of Indonesian unity, populist values ​​led by wisdom in deliberation, the value of social justice for all Indonesian people.